AGAMA DAN VIRTUALITAS (MENELISIK AKTIVITAS KHALAYAK DALAM FENOMENA SOSIAL DAN RITUAL KEAGAMAAN DI DUNIA VIRTUAL) - Zanniro Sururi Hsb (Ilmu Komunikasi UIN Alauddin Makassar, 2019)
Sophisticated information technology triggers audiences not only passively in receiving and seeking information / religious teachings, but far more active than before. The offers and promises made by technology make the audience in the drunken zone as if bringing themselves more glorifying technology. This paper seeks to express audience activity in the virtual world both in social phenomena and religious rituals. Based on the results of the study, the writer found two social phenomena including alusination and phubbing. Whereas the phenomenon of religious rhythmic is prayer and marriage contract via video call, Ustadz Googlian, virtual silaturrahmi, ZISWAF online, online Koran, and digital Koran. From social and religious phenomena shows that the sophistication of information technology brings opportunities and challenges, like a double-edged knife that brings benefits and sometimes on one hand brings harm to humans.